2020
DOI: 10.1101/2020.04.26.062422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quality control of low-frequency variants in SARS-CoV-2 genomes

Abstract: During the current outbreak of COVID-19, research labs around the globe submit sequences of the local SARS-CoV-2 genomes to the GISAID database to provide a comprehensive analysis of the variability and spread of the virus during the outbreak. We explored the variations in the submitted genomes and found a significant number of variants that can be seen only in one submission (singletons). While it is not completely clear whether these variants are erroneous or not, these variants show lower transition/transve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…It can be difficult to distinguish sequencing errors of different types from genuine transmitted and non-transmitted mutations in genome sequences. Taking a conservative approach, many researchers remove mutations that are observed only once during the evolution of the virus when constructing a phylogenetic tree, as these may be more likely to be errors [21,22] , or non-transmitted mutations. However, systematic errors, where the same error from a common source is introduced many times in otherwise distinct viral genome sequences, are not removed by that approach [23,24] .…”
Section: Figure 1: Effect Of Recurrent Sequencing Mutations On Phylogmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be difficult to distinguish sequencing errors of different types from genuine transmitted and non-transmitted mutations in genome sequences. Taking a conservative approach, many researchers remove mutations that are observed only once during the evolution of the virus when constructing a phylogenetic tree, as these may be more likely to be errors [21,22] , or non-transmitted mutations. However, systematic errors, where the same error from a common source is introduced many times in otherwise distinct viral genome sequences, are not removed by that approach [23,24] .…”
Section: Figure 1: Effect Of Recurrent Sequencing Mutations On Phylogmentioning
confidence: 99%
“…There are at least four possible sources of (real or apparent) mutations that recur within independent lineages in a tree, and each makes distinct predictions about the source of recurrent mutations (Table 1). In particular, recent work has shown a strong bias towards C>U mutation in the SARS-CoV-2 genome [21,[42][43][44] . Systematic errors, which usually result from consistent errors in molecular biology techniques or bioinformatic data data processing, need not reflect this bias and are not subject to natural selection.…”
Section: Systematic Error Could Be Mistaken For Recurrent Mutation Ormentioning
confidence: 99%
“…It can be difficult to distinguish sequencing errors of different types from genuine transmitted and non-transmitted mutations in genome sequences. Taking a conservative approach, many researchers remove variants that are observed only once during the evolution of the virus when constructing a phylogenetic tree, as these may be more likely to be errors [22,23] or non-transmitted mutations. However, systematic errors, where the same error from a common source is introduced many times in otherwise distinct viral genome sequences, are not removed by that approach [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…P-values are based on a two-tailed Fishers exact test. Rayko et al have reported a lower transition/transversion ratio in singleton SARS-CoV-2 genomic variations (that can only be seen in one genome submission) [13]. As a separate control, we looked at mutations that were identified in two or more independent genome assemblies.…”
Section: Resultsmentioning
confidence: 99%